Are Malaysian students ready to be authors of digital contents? a case study of digital library stakeholders readiness - Abrizah, Abdullah; Zainab, Awang Ngah (2007)
The paper reports on a study that ascertains the factors facilitating students to utilize digital libraries for educational purposes. The study investigates students ICT readiness, usage of online resources and information seeking behaviour of secondary school students with the specific goal of applying the results to the design of a collaborative digital library for school projects. The digital library has been conceived to support resource needs of these students as well provide the space for them to publish their school projects, which are currently submitted handwritten. The study uses the case study approach and an urban secondary school in Malaysia is chosen as the case school. Findings from a survey and focus group interviews indicate that the students are ready to collaboratively build the digital library resources as evidenced by students digital library readiness score of 31.4/40.